Survival of dominated strategies under evolutionary dynamics - William H. Sandholm; Josef Hofbauer (Theoretical Economics, 2011)
We prove that any deterministic evolutionary dynamic satisfying four mild requirements fails to eliminate strictly dominated strategies in some games. We also show that existing elimination results for evolutionary dynamics are not robust to small changes in the specifications of the dynamics. Numerical analysis reveals that dominated strategies can persist at nontrivial frequencies even when the level of domination is not small.
Keywords: C72; C73; 330; Evolutionary game theory; evolutionary game dynamics; nonconvergnece; dominated strategies